PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP AUDIT DELAY DENGAN KOMPETENSI KOMITE AUDIT SEBAGAI VARIABEL MODERATING - Marwanti, Tiwuk (Universitas Slamet Riyadi, 2015)
Every publicly traded companies listed on the Indonesia Stock Exchange (IDX) must submit audited financial statements to the Securities and Exchange Commission the results no later than 90 days after the publication of the annual financial statements. This study aimed to examine the effect of the characteristics of the company to audit delay with the competence of the audit committee as a moderating variable. The study population includes a manufacturing company in the Stock Exchange in 2012 – 2013 with samples taken by purposive sampling as many as 168 companies. The data collected was secondary data by the method of documentation. Before the first data analysis conducted analytical testing includes test multicollinearity, autocorrelation, heteroscedasticity test and test for normality. Methods of data analysis to test the hypothesis is multiple linear regression analysis, the coefficient of determination (R2), the F statistic test and t test. Analytical methods for moderating is interaction test. The results of this study indicate that the size of the company significant negative effect on audit delay. Solvency significant positive effect on audit delay. Competence of the audit committee, the profit / loss of the company and the size of the firm does not affect the audit delay. Keywords: audit delay, the size of the company, the audit committee competence, solvency, the size of the KAP